Pengembangan Media Beberan Jual Beli untuk Melatih Kecakapan Literasi Numerasi Siswa Tunarungu - Zakiyah, Zakiyah; Mustiana, Lailin (Jurnal Didaktika Pendidikan Dasar, 2024)
This study aims to determine the characteristics of the sale and purchase disclosure media to be developed, to test the feasibility of the buying and selling disclosure media, and to test the effectiveness of the use of buying and selling disclosure media on the results of students' numeracy literacy skills. This type of research is Research and development (R & D). The product of development in this research is the media of buying and selling information, namely the development of buying and selling statements to train numeracy literacy skills. The research design using the ADDIE approach was developed by Dick and Carry. To design a learning system with 5 development phases including: Analysis, Design, Development or Production, Implementation or Delivery and Evaluations with qualitative and quantitative data analysis. The development of buying and selling information media was carried out at SLBN Seduri Mojokerto in August-September in the odd semester of the 2021/2022 academic year. The data sources for this research were 4th grade deaf students. The results of expert validation in this development research obtained a validity percentage of 82, 3, the development of the media for selling and selling, the student response value was obtained at 78, the results of the analysis obtained good results. So it can be concluded that the results of the media disclosure of buying and selling are effectively used.